Impact of Pathological Grades of Metabolic Dysfunction-Associated Steatotic Liver Disease on Weight Loss Following Laparoscopic Sleeve Gastrectomy - Qu YF; Wang K; Li Y; Cheng YG; Hu SY; Zhong MW (Diabetes, Metabolic Syndrome and Obesity, 2025)
Yun-Fei Qu,1,* Kang Wang,1,* Yue Li,2 Yu-Gang Cheng,1,3 San-Yuan Hu,1,3 Ming-Wei Zhong1,3 1Department of General Surgery, The First Affiliated Hospital of Shandong First Medical University & Shandong Provincial Qianfoshan Hospital, Jinan, Shandong, 250000, People’s Republic of China; 2Department of General Surgery, Shandong Provincial Qianfoshan Hospital, Cheeloo College of Medicine Shandong University, Jinan, Shandong, 250000, People’s Republic of China; 3Medical Center for Digestive Diseases, The First Affiliated Hospital of Shandong First Medical University & Shandong Provincial Qianfoshan Hospital, Jinan, Shandong, 250000, People’s Republic of China*These authors contributed equally to this workCorrespondence: San-Yuan Hu, Email husanyuan1962@hotmail.com Ming-Wei Zhong, Email zmwgz@126.comPurpose: The impact of hepatic steatosis severity on postoperative weight loss outcomes remains unclear. This study aimed to evaluate the effect of fatty liver severity on percentage of excess weight loss (%EWL) in patients undergoing laparoscopic sleeve gastrectomy (LSG).Methods: This retrospective cohort study included 226 patients with obesity who underwent LSG. Baseline data included liver biopsy grade (mild, moderate, or severe), body mass index (BMI), liver function, and metabolic parameters. Postoperative outcomes were assessed at 1, 3, 6, and 12 months. Statistical methods included the Pearson and Spearman correlations, chi-square test, Kruskal–Wallis test, general linear models, Kaplan–Meier analysis, and multivariate regression to identify the predictors of weight loss and cumulative rates of achieving 50% EWL and to plot the cumulative incidence curve.Results: Baseline BMI, homeostasis model assessment for insulin resistance, free fatty acids, and A1C levels were significantly associated with steatosis severity (P < 0.05). Severe metabolic dysfunction-associated steatotic liver disease (MASLD) was associated with a lower %EWL at 1, 3, 6, and 12 months (1 month %EWL: 32.34% vs 38.59% in the mild group; P < 0.05). The Kaplan–Meier analysis showed delayed achievement of 50% EWL in the severe group (P < 0.05). Multivariate regression analysis identified MASLD severity and preoperative BMI as independent predictors of %EWL. General linear models confirmed the significant dynamic effects of MASLD severity on weight loss over time (P < 0.05).Conclusion: MASLD severity significantly affects postoperative weight loss and delays the achievement of optimal outcomes, especially in the early postoperative period. Preoperative evaluation of liver pathology is essential for optimizing surgical outcomes in patients with obese having MASLD.Keywords: obesity, fatty liver, bariatric surgery, insulin resistance